Feminist view in Emily Dickinson's selected poems - Arsyad, Nisrina Muthi'ah; Salsabillah, Tiara Auliya (Yayasan Mitra Persada Nusantara, 2024)
The study focuses on Emily Dickinson’s poems that express feminist views and societal expectations toward women. The selected poems, “They Shut Me Up in Prose –” and